CD4/CD8 ratio and CD8 counts predict CD4 response in HIV-1-infected drug naive and in patients on cART. Issue 42 (October 2016) - Sauter, Rafael; Huang, Ruizhu; Ledergerber, Bruno; Battegay, Manuel; Bernasconi, Enos; Cavassini, Matthias; Furrer, Hansjakob; Hoffmann, Matthias; Rougemont, Mathieu; Günthard, Huldrych F; Held, Leonhard
Abstract : Abstract: Plasma HIV viral load is related to declining CD4 lymphocytes. The extent to which CD8 cells, in addition to RNA viral load, predict the depletion of CD4 cells is not well characterized so far. We examine if CD8 cell count is a prognostic factor for CD4 cell counts during an HIV infection. A longitudinal analysis is conducted using data from the Swiss HIV cohort study collected between January 2000 and October 2014. Linear mixed regression models were applied to observations from HIV-1-infected treatment naive patients (NAIVE) and cART-treated patients to predict the short-term evolution of CD4 cell counts. For each subgroup, it was quantified to which extent CD8 cell counts or CD4/CD8 ratios are prognostic factors for disease progression. In both subgroups, 2500 NAIVE and 8902 cART patients, past CD4 cells are positively ( P  < 0.0001) and past viral load is negatively ( P  < 0.0001) associated with the outcome. Including additionally past CD8 cell counts improves the fit significantly ( P  < 0.0001) and increases the marginal explained variation 31.7% to 40.7% for the NAIVE and from 44.1% to 50.7% for the cART group. The past CD4/CD8 ratio (instead of the past CD8 level) is positively associated with the outcome, increasing the explained variation further to 41.8% for NAIVE and 51.9% for cART. Abstract : Supplemental Digital Content is available in the text